Older people’s perceived autonomy in residential care: an integrative review - Moilanen Tanja; Kangasniemi Mari; Papinaho Olli; Mynttinen Mari; Siipi Helena; Suominen Sakari; Suhonen Riitta (SAGE Publications, 2022)
Autonomy has been recognised as a key principle in healthcare, but we still need to develop a consistent understanding of older people’s perceived autonomy in residential care. This study aimed to identify, describe and synthesise previous studies on the perceived autonomy of older people in residential care. Ethical approval was not required, as this was a review of published literature. We carried out an integrative review to synthesise previous knowledge published in peer-review journals in English up to September 2019. Electronic and manual searches were conducted using the CINAHL, Philosopher’s Index, PubMed, SocINDEX, Scopus and Web of Science databases. The data were analysed using the constant comparison method. The review identified 46 studies. Perceived autonomy referred to the opportunities that older people had to make their own choices about their daily life in residential care, and achieving autonomy promoted both health and quality of life. Autonomy was linked to older people’s individual capacities, including their level of independence, physical and mental competence, personal characteristics, and whether relatives shared and supported their perceived autonomy. Professionals could facilitate or hinder older peoples’ autonomy in a number of ways, including providing opportunities for autonomy, how daily care needs and activities were managed, and controlling older people’s choices. Professionals’ characteristics, such as education and attitudes, and the older people’s living environments were also associated with their perceived autonomy and included organisational characteristics and physical and social care facilitators. Older people’s perceived autonomy promoted health and quality of life in residential care. However, their autonomy was associated with a number of protective and restrictive individual and environmental factors, which influenced whether autonomy was achieved.